2014
DOI: 10.1080/15299732.2013.856370
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Cambridge Depersonalization Scale in Puerto Rico

Abstract: Depersonalization experiences have been studied in the United States and Europe, but there is a dearth of investigations with Latino populations. In the current study we examined the psychometric properties of the Spanish version of the Cambridge Depersonalization Scale (CDS) in 300 adult individuals from the community and compared the results with those reported previously with non-Latino clinical populations. Discrepant findings have been reported with respect to the factor structure of the CDS. We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…(2 By contrast, higher dynamical and embodied engagements with the surroundings should lead to lower depersonalization. Our findings seem to provide a significant support for (1) and a weak significant support for (2). Indeed, we found a weak significant negative correlation between the frequency of physical exercise during the lockdown and the occurrence of depersonalisation experiences.…”
Section: Discussionsupporting
confidence: 62%
“…(2 By contrast, higher dynamical and embodied engagements with the surroundings should lead to lower depersonalization. Our findings seem to provide a significant support for (1) and a weak significant support for (2). Indeed, we found a weak significant negative correlation between the frequency of physical exercise during the lockdown and the occurrence of depersonalisation experiences.…”
Section: Discussionsupporting
confidence: 62%
“…Responses are made on a scale from 0 ( Never ) to 4 ( All the time ) with higher scores representing a greater frequency of depersonalization experiences. Factor analyses of the CDS have demonstrated that the scale is multidimensional with studies reporting on two (Blevins, Witte, & Weathers, 2013 ), four (Apontze-Soto, Vélez-Pastrana, Martínez-Taboas, & González, 2014 ; Sierra, Baker, Medford, & David, 2005 ), and five factors (Simeon, Smith, Knutelska, & Smith, 2008 ). Due to the replication and conciseness of the original four factor solution, the current study reports subscale scores for Anomalous Body Experience (nine items; e.g., “Seeing oneself outside, as if looking in a mirror”; α =0.94), Emotional Numbing (six items; e.g., “No emotions felt when weeping or laughing”; α =0.87), Alienation from Surroundings (four items; e.g., “Surroundings feel detached or unreal”; α =0.86), and Anomalous Subjective Recall (five items; e.g., “Personal memories feel as though one has not been involved in them”; α =0.85).…”
Section: Methodsmentioning
confidence: 99%
“…Although our study did not directly investigate this issue, our sample exhibited much higher DP scores compared to what has typically been observed in samples obtained before the COVID-19 lockdown. For example, Aponte-Soto et al 76 published a study with 300 Italian participants where they reported an average general score in CDS-29 of M = 16.3 ( SD = 18.3, range = 0–132). They also reported that only 2% (6 participants) obtained a score of ≥ 70 indicating, according to them, clinically significant DP symptoms.…”
Section: Discussionmentioning
confidence: 99%